Attenuation of subchondral bone abnormal changes in osteoarthritis by inhibition of SDF-1 signaling. Issue 6 (June 2017) - Chen, Y.; Lin, S.; Sun, Y.; Guo, J.; Lu, Y.; Suen, C.W.; Zhang, J.; Zha, Z.; Ho, K.W.; Pan, X.; Li, G.
Summary: Background: Current conservative treatments for osteoarthritis (OA) are largely symptoms control therapies. Further understanding on the pathological mechanisms of OA is crucial for new pharmacological intervention. Objective: In this study, we investigated the role of Stromal cell-derived factor-1(SDF-1) in regulating subchondral bone changes during the progression of OA. Methods: Clinical samples of different stages of OA severity were analyzed by histology staining, micro-CT, enzyme-linked immunosorbent assay (ELISA) and western blotting, to compare SDF-1 level in subchondral bone. The effects of SDF-1 on human mesenchymal stem cells (MSCs) osteogenic differentiation were evaluated. In vivo assessment was performed in an anterior cruciate ligament transaction plus medial meniscus resection in the SD rats. The OA rats received continuous infusion of AMD3100 (SDF-1 receptor blocker) in osmotic mini-pump implanted subcutaneously for 6 weeks. These rats were then terminated and subjected to the same in vitro assessments as human OA samples. Results: SDF-1 level was significantly elevated in the subchondral bone of human OA samples. In the cell studies, the results showed SDF-1 plays an important role in osteogenic differentiation of MSCs. In the OA animal studies, there were less cartilage damage in the AMD3100-treated group; microCT results showed that the subchondral bone formation was significantly reduced and so did the number of positive Nestin or Osterix cells in the subchondral bone region. Conclusions: Higher level of SDF-1 may induce the subchondral bone abnormal changes in OA and inhibition of SDF-1 signaling could be a potential therapeutic approach for OA.